Eel Gumne Aquaculture Farm Resort an integrated tourism destination in General Santos City Bay Area - Castillo, Psyche Desiree Een E.; Santos, Romeo B. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
It is ideal, if not imperative that General Santos City grow in a sustainable manner. The City dubbed as the Tuna Capital of the Philippines and the Home of Champions, is facing issues regarding its future. Rapid economic growth in the city puts pressure to its fragile environment. True and felt economic development is a concern for the city's working class and marginalized sector composed primarily of farmers, fisher folk, those working for the services sector and the people belonging minority ethnic groups. Gensan's history is celebrated in annual spectacles but seldom represented and immortalized in city art and architecture. The flagship tuna industry needs to have a supporting alternative and the city has looked into tourism and aquaculture to be potential development areas. The Eel Gumne Aquaculture Resort is a project in Gensan that integrates tourism with aquaculture along with culinary, cultural, and rural tourism. The integration of these tourism types as derived from the city and the project site's context form a tourism destination that is essentially community and resource-based. This development is envisioned to embody conservation of environment and culture at its core, while still remaining to be economically viable. It is a destination where visitors and the local of Gensan can experience Gensan's natural gifts and local authentic culture not revolving around just tuna and boxing. It is a destination where they can see Gensan's overlooked rich heritage and albeit fragile environment.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Tourism -- General Santos City -- Philippines; Aquaculture -- General Santos City -- Philippines